The diagnostic value of endometrial cytology in diagnosing endometrial pathology - Nadezhda Hinkova; Kamelia Tsvetanova; Tihomir Totev; Margarita Nikolova; Teodora Semova; Dimitar Dimitrov; Elitsa Petkova (Journal of Biomedical & Clinical Research)
Endometrial carcinoma remains one of the leading places in terms of frequency among oncogynecological diseases, both in countries with developed primary and secondary prevention and in countries with poorly functioning prevention. The implementation of screening programs would lead to the detection of oncological diseases in outpatient settings at an early stage, which would lead to positive socio-economical effects for society. This study aims to determine the test’s validity through the following criteria: sensitivity, specificity, and negative and positive predictive value of endometrial cytology compared with the histological result of examined tissue samples. We studied 300 women with abnormal uterine bleeding examined at the Clinic of Obstetrics and Gynecology at Saint Marina University Hospital– Pleven. Specimens for endometrial cytology were taken from all patients before invasive intervention. We compared the cytological results to evaluate the test validity, including sensitivity, specificity, and negative and positive predictive value in the cases with endometrial carcinoma. Statistical data processing was performed using the software programs MS Office Excel 2019 and IBM SPSS Statistics 28.0. The significance of results, findings and conclusions was determined at p < 0.05. A comparative analysis was performed on the cytological and histological results we obtained before and after the invasive manipulation. The study found statistical significance between the Pipelle biopsy results and cytological results (χ2 = 50.05, df = 24, p = 0.01, Cramer’s v = 0.439). Data analysis showed that endometrial cytology had a high specificity in proving endometrial carcinoma and a low positive predictive value (Se = 80%; Sp = 98%; PV = 66.7%; NV = 96.9%). Endometrial cytology could be an effective diagnostic method and can be applied to diagnose endometrial pathology. The combination of the two methods - cytological examination and transvaginal ultrasound would undoubtedly improve the detection rate of endometrial carcinoma. Additionally, cytology is an appropriate outpatient procedure that can be recommended for endometrial screening, especially in patients at high risk of developing endometrial cancer.